Pengaruh Lingkungan Kerja, Motivasi Kerja Dan Pemberian Insentif Terhadap Kinerja Guru (Studi Pada Sekolah Sdit Pelita Alam) - Nurul Huda; Ibnu Haris Nasution (Prisani Cendekia, 2023)
One of the efforts to improve the quality of education is to improve the quality of human resources teaching staff. This study aims to analyze the effect of the work environment, work motivation, and incentives on teacher performance at SDIT Pelita Alam Pondok Gede Bekasi. The method used in this research is quantitative research, with a sample of 40 respondents. Methods of data collection using a questionnaire with a Likert scale. The data obtained were then analyzed using SPSS version 25. The results of this study showed that the work environment had a positive and insignificant effect on teacher performance at SDIT Pelita Alam (p = 0.274 > 0.05), work motivation had a positive and not significant effect on teacher performance at SDIT Pelita Alam (p = 0.74 > 0.05), incentives had a positive and insignificant effect on teacher performance at SDIT Pelita Alam (p = 0.235 > 0.05). The work environment, work motivation, and provision of incentives simultaneously have an influence on teacher performance at SDIT Pelita Alam, which is equal to 35.1%.